New Zealand's energy policy from the world system perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Debahasatin, Jutha (Massey University, 1994)
The World-System Theory of Immanuel Wallerstein is a grand-scale theory that is useful as a framework to understand how New Zealand's path of development has been affected by the country's energy policy. The theory is appropriate in application to energy issues because its macro-level of analysis puts emphasis on both exogenous and endogenous factors. Its special emphasis on historical background and context also adds to an understanding of the New Zealand position. The World-System perspective offers three major concepts directly applicable to the case of New Zealand energy policy, namely, the interplay between politics and economics with a particular interest in the role of multinational corporations (MNCs) and the state, the notion of semiperiphery, and the cyclical nature of the world economy. During the period of the 1970s economic downturn marked by two oil crises, New Zealand as well as most other countries and the MNCs suffered a severe setback. However, while most core states, as well as some successful non-core states and the oil majors, could react appropriately to the crises and retain their potential for growth, the semiperipheral New Zealand could not. The country possessed few options because of her intermediate level of industrialisation and less competent state apparatus compared to the MNCs involved. Lacking the intention to promote local industrial capitalists, the New Zealand state chose wrong strategies, first Think Big and then disinvestment, which together have undermined the bargaining position of local entrepreneurs, over-committed the national hydrocarbon resource and disproportionately promoted the interest of the foreign oil corporations. The overall outcome of the energy policy is therefore detrimental to the country's development.
Keywords: New Zealand; Energy policy; Power resources; Economic policy; Economic history -- 1945-